2014
DOI: 10.1016/j.cub.2014.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Assembling the Protein Architecture of the Budding Yeast Kinetochore-Microtubule Attachment using FRET

Abstract: Background The kinetochore is a multiprotein machine that couples chromosome movement to microtubule (MT) polymerization and depolymerization. It uses numerous copies of at least three MT-binding proteins to generate bidirectional movement. The nanoscale organization of these proteins within the kinetochore plays an important role in shaping the mechanisms that drive persistent, bidirectional movement of the kinetochore. Results We used Förster Resonance Energy Transfer (FRET) between genetically encoded flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
114
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(133 citation statements)
references
References 50 publications
15
114
1
Order By: Relevance
“…The N-terminal tail of Ndc80 cross-linked to multiple regions of the complex (Figure S2,C and D). This is consistent with the extended length of the tail (at least 15 nm, Aravamudhan et al 2014) and its predicted disordered nature (Wei et al 2005(Wei et al , 2007Ciferri et al 2008;Alushin et al 2010), allowing it to reach multiple parts of the complex in a cross-linking reaction.…”
Section: The S Cerevisiae Ndc80 Complex Can Adopt a Tightly Folded Csupporting
confidence: 64%
See 2 more Smart Citations
“…The N-terminal tail of Ndc80 cross-linked to multiple regions of the complex (Figure S2,C and D). This is consistent with the extended length of the tail (at least 15 nm, Aravamudhan et al 2014) and its predicted disordered nature (Wei et al 2005(Wei et al , 2007Ciferri et al 2008;Alushin et al 2010), allowing it to reach multiple parts of the complex in a cross-linking reaction.…”
Section: The S Cerevisiae Ndc80 Complex Can Adopt a Tightly Folded Csupporting
confidence: 64%
“…It was previously proposed that the loop acts as a hinge, conferring the flexibility observed for recombinant Ndc80 complexes on negative-stain electron micrographs (Wang et al 2008). Super-resolution microscopy experiments further suggested that different conformations of the Ndc80 complex exist in vivo; the distance between the two ends of the Ndc80 complex decreases from $40 nm to $20 nm during the metaphaseto-anaphase transition in S. cerevisiae (Aravamudhan et al 2014). Altogether, these results predict that the Ndc80 complex undergoes a conformational change through bending at the loop region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deleting the loop domain of Ndc80 causes lethality, suggesting that flexibility of the complex is necessary in vivo (12). Additional in vivo evidence suggests that a folded Ndc80 complex is important during early mitosis whereas an elongated conformation exists at metaphase (8)(9)(10). We propose that the Ndc80 complex adopts different conformations to modulate the strength of its microtubule attachment.…”
Section: Mind Activates Microtubule Binding By Ndc80c Via a Mechanismmentioning
confidence: 99%
“…Additionally, substantial evidence suggests that the outer kinetochore Ndc80 complex undergoes conformational changes throughout mitosis (8)(9)(10). The Ndc80 complex hinges about a flexible "loop" region and exists in both a folded conformation and an elongated state (8,11).…”
Section: Significancementioning
confidence: 99%